2008
DOI: 10.1111/j.1600-0714.2008.00657.x
|View full text |Cite
|
Sign up to set email alerts
|

Head and neck squamous cell carcinoma in non‐smoking and non‐drinking patients with multiple tumors: etiologic significance of p53 and Ki‐67 in non‐tumorous epithelium

Abstract: Non-smoking and non-drinking patients with squamous cell carcinoma have the same risk for developing multiple tumors as their smoking and drinking counterparts. As this occurs without an increased expression of p53 or Ki-67, the significance of these proteins as biomarkers indicating pre-malignant mucosal alterations is doubtful. Further research is needed to clarify this predisposition for developing multiple head and neck cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 25 publications
2
29
0
Order By: Relevance
“…The majority of studies about p53 in OSCC have focused on protein expression by immunohistochemistry [6,8,9,10,11,17]. Some of these studies [22,23,24] include tumors affecting head and neck cancer as a whole, others are more specific and analyze p53 expression only in the mouth [25,26,27]. In the present study a population of patients diagnosed with primary OSCC was analyzed in order to obtain a more specific result.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies about p53 in OSCC have focused on protein expression by immunohistochemistry [6,8,9,10,11,17]. Some of these studies [22,23,24] include tumors affecting head and neck cancer as a whole, others are more specific and analyze p53 expression only in the mouth [25,26,27]. In the present study a population of patients diagnosed with primary OSCC was analyzed in order to obtain a more specific result.…”
Section: Discussionmentioning
confidence: 99%
“…The situation is worse in developing countries, such as India, Thailand and Brazil, 3 where this cancer is more common. 4 The mean survival rate in these patients is 5 years. 5 The 5-year life expectancy is about 50% when there are lymph node metastases.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 No significant increase in survival rates had occurred in the last few decades in spite of new surgical techniques, radiotherapy and concomitant chemotherapy. 4,5,6,8 Epidemiologic studies have suggested a multifactor etiology for this cancer; these predisposing factors include smoking, alcohol use, human papilloma virus (HPV) infection, and genetic factors. 1,4,7,9,10 Genetic polymorphisms leading to folate deficiency appear to facilitate the onset and growth of head and neck squamous cell carcinoma and other types of cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Currently, there is no reliable method to predict which of the patients will develop SPT. These tumors may appear due to extensive initiation and promotion by various carcinogens mainly tobacco and alcohol, leaving to a widespread disorder of the epithelial maturation and differentiation with a field effect.…”
mentioning
confidence: 99%